The Diary of Jack the Ripper - Edited by Harrison, Shirley (London Smith Gryphon Publishers, 1996)
Tells the story of how the diary was tested and examined. This new edition has been updated to include the latest research. The diary itself is reproduced in full, so that readers can assess for themselves the words of Jack the Ripper across the abyss of more than a century
Include Index
Keywords: Jack, the Ripper -- Murderers -- Serial murderers